A Method of Judging the State Time Point of Mechanical Characteristic Switch. Issue 4 (January 2021) - Tang, Qi; Wu, Lihui; Luo, Rongbo; Li, Guowei; Wang, Junbo; Liu, Shaohui
Abstract: Aiming at the problem of judging the opening / closing time node by directly detecting the switch quantity in the process of detecting the mechanical characteristics of the switch cabinet, this paper puts forward a method to calculate the opening / closing time node with the CT secondary current as the original data. This method through the acquisition of CT secondary side current, current data of any phase, calculating threshold, intercepting alternative data, calculating slope and rate of change, the time node of opening and closing is obtained, solve many scenarios acquisition switch quantity and difficulties, judgement open/close time and the problem of low accuracy of switch performance. Through practical application, compared with the traditional acquisition of switch quantity to judge the opening / closing time node, the method proposed in this paper has universality, low detection difficulty and high judgment accuracy of opening / closing time node.